The Use of ChatGPT In Writing: English Students Perception and Satisfaction - Yulistyawan, Farhan; Halim, Abdul; Puspita, Rani Herning (FKIP Unismuh Makassar, 2025)
Chat GPT, a generative language model recently created by OpenAI, has received widespread criticism from people around the world. ChatGPT illustrates both the potential opportunities and challenges in education. This research aims to investigate the nuances of students' use of ChatGPT, an AI-powered English writing assistant, with a focus on their opinions, experiences, and overall happiness. Because of its potential to enhance students' writing abilities, the use of artificial intelligence (AI) as an English writing assistant has drawn attention as the field continues to transform the educational landscape. using semi-structured interviews and a qualitative method approach. Uncovering the complex elements that influence students' opinions on ChatGPT is the goal of this study. To give a thorough knowledge of the tool's efficacy, the research will examine the user interface, adaptation to different writing styles, and the perceived influence on writing skill.